The value of 3D pseudo-continuousarterial spin labeling perfusion imaging in moyamoya disease—Comparison with dynamic susceptibility contrast perfusion imaging - Zhang, Hongtao; Lu, Mingming; Liu, Shitong; Liu, Dongqing; Shen, Xuxuan; Sheng, Fugeng; Han, Cong; Cai, Jianming (Frontiers in Neuroscience, 2022)
Background and Purpose: 3D pseudo-continuous arterial spin labeling (3D pCASL) is commonly used to measure arterial cerebral blood flow (CBF). The aim of this study was to assess the clinical feasibility and accuracy of 3D pCASL in comparison with dynamic susceptibility contrast (DSC) perfusion imaging in moyamoya disease (MMD). Materials and methods: 174 MMD patients underwent 3D pCASL and DSC-MRI for evaluating cerebral blood perfusion. 3D-pCASL with two single post labeling delay time (1500 ms and 2500 ms) was used to measure CBF. The values of DSC-CBF and ASL-CBF were calculated for major arterial territories including the anterior, middle and posterior cerebral arteries as well as areas based on the Alberta Stroke Program Early CT Score (ASPECTS) template. The correlation between DSC-CBF and ASL-CBF was analyzed. The consistency and accuracy between the two methods in assessing the cerebral ischemic state before and after surgery were analyzed. Results: Correlation between ASL (2500 ms) and DSC-MRI was slightly better than correlation between ASL (1500 ms) and DSC-MRI in major vascular territories before revascularization. Significant correlations were observed between ASL (2500 ms) and DSC-MRI and between ASL (1500 ms) and DSC-MRI in major vascular territories after revascularization. For 44 surgically treated patients, the scores of ASPECTS for CBF on the operated side were significantly different before and after revascularization (p<0.05) and good consistency respectively on all the examination methods. Comparison of the scores of ASPECTS of the three parameters before and after revascularization showed that there was no statistical difference between them (p>0.05). Conclusion: Compared to DSC-MRI, 3D pCASL can assess the cerebral blood perfusion in MMD before and after revascularization effectively. 3D pCASL showed feasibility and clinical utility value in MMD patients.